SOSIALISASI PAMFLET PARENTING TENTANG PSIKOLOGI PADA ANAK DALAM MENGHADAPI PERKEMBANGAN ZAMAN MODERN - Trisnaninigsih, Rahma; Urrahman, Dhiya; Isnugroho, Hernawan (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2023)
Some parents feel that the development of the times can have a bad influence on children, for example, technological sophistication. In fact, technological sophistication cannot be avoided even technology is able to help children complete their school assignments. However, parents can supervise and educate children according to the time and age, as in today's digital era. Digital Parenting is an innovative parenting method for raising children in an all-digital era, this ability needs to be owned by parents in this digitally absorbing era and fast access to information like now. Technology and internet differences bring positive and negative sides to the challenges faced by parents in raising their children.